2015
DOI: 10.1097/md.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Air pollution Increases the Risk of Osteoporosis

Abstract: Several studies have indicated that air pollution induces systemic as well as tissue-specific inflammation. Chronic inflammatory diseases such as rheumatoid arthritis and chronic obstructive pulmonary disease reduce bone mineral density (BMD), leading to increased release of immune cells from the bone marrow. However, the association between air pollution and osteoporosis remains poorly defined. Therefore, we conducted this population-based retrospective cohort study to evaluate the risk of osteoporosis in Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 34 publications
3
46
1
Order By: Relevance
“…58 Also, Chang et al found an association between air pollution (carbon monoxide and nitrogen dioxide) and increased risk of osteoporosis. 57 The difference in observed associations across multiple anatomical sites might be explained by differential anatomical susceptibility to the effects of PM on bones. 59 Alvaer et al reported gender differences in the association between air pollution and BMD, with association observed only for men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Also, Chang et al found an association between air pollution (carbon monoxide and nitrogen dioxide) and increased risk of osteoporosis. 57 The difference in observed associations across multiple anatomical sites might be explained by differential anatomical susceptibility to the effects of PM on bones. 59 Alvaer et al reported gender differences in the association between air pollution and BMD, with association observed only for men.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other air pollutants such as carbon monoxide (CO) and nitrogen dioxide (NO 2 ) have been previously associated with bone loss and osteoporosis. 42,57 Unfortunately, we did not have access to CO and NO 2 exposure data in for the Medicare study nor for BACH/Bone, limiting our capability to explore these associations. Further analyses to evaluate the role PM 2.5 and BC, as well as of CO and NO 2 on bone health are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have tried to use COPD as a proxy variable for cigarette smoking, which has been accepted previously in several studies. [30][31][32][33] Third, the accuracy of diagnoses based on administrative data is another issue of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, lung cancer is considered the major severe disease caused by air pollution [1,2]. Notably, accumulating evidence shows that chronic exposure to air pollution is associated with not only respiratory diseases but also non-lung cancers [3,4] and cardiovascular [5,6], inflammatory [7,8], and neurodegenerative diseases [9,10] including age-related macular degeneration (AMD) [11].…”
Section: Introductionmentioning
confidence: 99%